STRATEGI MARKETING DESA WISATA BERBASIS DIGITAL - Chotijah Fanaqi; Ummu Salamah; Devi Gusara Rahmadhan (Commed : Jurnal Komunikasi dan Media, 2022)
This study aims to look at the model of using digital media as a marketing strategy for Sindangkasih Tourism Village. This study uses a qualitative approach using the theory of Marketing Public Relations Strategy which gave birth to a three-way strategy which consists of the Pull Strategy, Push Strategy, and Pass Strategy. The data collection techniques used observation, interviews, and documentation. The informants came from the managers and visitors of the Sindangkasih Tourism Village. Meanwhile, the resource persons came from academics in the field of digital marketing and the Garut Regency Tourism Office. The results of this study indicate that in its digital marketing strategy, Sindangkasih Tourism Village uses a three-way strategy which includes a pull, push, and pass strategy. In the pull strategy, the manager utilizes a digital base including websites and social media, especially Instagram. The push strategy applies several ways, namely by personal selling, collaboration with travel parties, and giving bonuses to those who participate in providing promotions related to the Sindangkasih Tourism Village. While the strategy pass is by holding Sapta Pesona, events, and cooperation with third parties in covering activities held by Sindangkasih Tourism Village such as mass media and sharing content with visitors.